Decay of bound states in the continuum of Majorana fermions induced by vacuum fluctuations: Proposal of qubit technology - Ricco, L. S. [UNESP]; Marques, Y. [UNESP]; Dessotti, F. A. [UNESP]; Machado, R. S. [UNESP]; De Souza, M. [UNESP]; Seridonio, A. C. [UNESP] (American Physical Society (APS), 2016)
We report on a theoretical investigation of the interplay between vacuum fluctuations, Majorana quasiparticles (MQPs), and bound states in the continuum (BICs) by proposing a new venue for qubit storage. BICs emerge due to quantum interference processes as the Fano effect and, since such a mechanism is unbalanced, these states decay as regular into the continuum. Such fingerprints identify BICs in graphene as we have discussed in detail in Phys. Rev. B 92, 245107 (2015)10.1103/PhysRevB.92.245107 and Phys. Rev. B, 92, 045409 (2015)10.1103/PhysRevB.92.045409. Here, by considering two semi-infinite Kitaev chains within the topological phase, coupled to a quantum dot (QD) hybridized with leads, we show the emergence of a novel type of BICs, in which MQPs are trapped. As the MQPs of these chains far apart build a delocalized fermion and qubit, we identify that the decay of these BICs is not connected to Fano and it occurs when finite fluctuations are observed in the vacuum composed by electron pairs for this qubit. From the experimental point of view, we also show that vacuum fluctuations can be induced just by changing the chain-dot couplings from symmetric to asymmetric. Hence, we show how to perform the qubit storage within two delocalized BICs of MQPs and to access it when the vacuum fluctuates by means of a complete controllable way in quantum transport experiments.